Cognitive Impairment and Age-Related Vision Disorders: Their Possible Relationship and the Evaluation of the Use of Aspirin and Statins in a 65 Years-and-Over Sardinian Population - Mandas, Antonella; Mereu, Rosa Maria; Catte, Olga; Saba, Antonio; Serchisu, Luca; Costaggiu, Diego; Peiretti, Enrico; Caminiti, Giulia; Vinci, Michela; Casu, Maura; Piludu, Stefania; Fossarello, Maurizio; et al. (Frontiers in Aging Neuroscience, 2014)
Neurological disorders (Alzheimer’s disease, vascular and mixed dementia) and visual loss (cataract, age-related macular degeneration, glaucoma and diabetic retinopathy) are among the most common conditions that afflict people of at least 65 years of age. An increasing body of evidence is emerging which demonstrates that memory and vision impairment are closely, significantly and positively linked and that statins and aspirin may lessen the risk of developing age-related visual and neurological problems. However, clinical studies have produced contradictory results. Thus, the intent of the present study was to reliably establish whether a relationship exist between various types of dementia and age-related vision disorders, and to establish whether statins and aspirin may or may not have beneficial effects on these two types of disorders. We found that participants with dementia and/or vision problems were more likely to be depressed and displayed worse functional ability in basic and instrumental activities of daily living than controls. Mini mental state examination scores were significantly lower in patients with vision disorders compared to subjects without vision disorders. A closer association with macular degeneration was found in subjects with Alzheimer’s disease than in subjects without dementia or with vascular dementia, mixed dementia or other types of age-related vision disorders. When we considered the associations between different types of dementia and vision disorders and the use of statins and aspirin, we found a significant positive association between Alzheimer’s disease and statins on their own or in combination with aspirin, indicating that these two drugs do not appear to reduce the risk of Alzheimer’s disease or improve its clinical evolution and may, on the contrary, favor its development. No significant association in statin use alone, aspirin use alone or the combination of these was found in subjects without vision disorders but with demen